Postdiagnosis body mass index and risk of mortality in colorectal cancer survivors: a prospective study and meta-analysis - Schlesinger, Sabrina; Siegert, Sabine; Koch, Manja; Walter, Jessica; Heits, Nils; Hinz, Sebastian; Jacobs, Gunnar; Hampe, Jochen; Schafmayer, Clemens; Nöthlings, Ute (Cancer causes & control, 2014)
Purpose: Aim of this study was to investigate the association between postdiagnosis body mass index (BMI) and all-cause mortality in colorectal cancer (CRC) survivors in a prospective study and meta-analysis. Methods: We conducted a prospective cohort study on 2,143 CRC survivors in Germany. Participants were recruited to the study on average 4 years after diagnosis, and postdiagnosis BMI was assessed at recruitment using a self-administered questionnaire. CRC survivors were followed up for a mean time of 3.5 years. The association between BMI and all-cause mortality was investigated using multivariable Cox proportional hazards models. Additionally, we performed a meta-analysis of studies on postdiagnosis BMI and all-cause mortality (n = 5, including this study) by applying random-effects models. Results: In the prospective analysis, 349 participants died. BMI was not statistically significantly associated with all-cause mortality. Compared to normal weight survivors, the hazard ratios (HRs) [95 % confidence interval (CI)] for all-cause mortality in underweight, overweight and obese survivors were 1.65 (0.79–3.45), 0.80 (0.62–1.03) and 0.84 (0.62–1.14), respectively. In the meta-analysis, individuals with underweight were at increased risk for all-cause mortality [HR (95 % CI) 1.72 (1.18–2.49)], whereas individuals with overweight had a lower risk [HR (95 % CI) 0.79 (0.71–0.88)], compared to normal weight subjects. For obesity, the risk of mortality was also reduced with only borderline significance [HR (95 % CI) 0.88 (0.77–1.00)]. Conclusions: While the present study as well as single previously published studies showed that overweight was associated with a non-significant reduced risk for all-cause mortality, our meta-analysis indicated a decreased mortality risk among overweight CRC survivors.